VD_FINDINFO HC / 2022 / 664 vom 19. August 2022 - VD Tribunal cantonal (2022)
RESTITUTION DU DÉLAI, FAUTE LÉGÈRE, INCAPACITÉ DE TRAVAIL, MALADIE, REJET DE LA DEMANDE, DROIT D'ÊTRE ENTENDU | 148 al. 1 CPC, 149 CPC (CH)